The Elasticity of Agricultural Income in the EU Member States Under Different Cost Structures - Kryszak, Łukasz; Staniszewski, Jakub (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2017)
The aim of this paper was to determine whether the EU countries which vary in terms of their cost structure in agriculture, differ also with regard to the influence of capital-labour ratio and land supply per worker on labour profitability. It was assumed that data concerning the presence and character of those differences can contribute to better understanding of the nature of agricultural development in the EU countries. The main sources of data used in this paper were the Economic Accounts for Agriculture (Eurostat) and the FAOStat database. The study covered the period of 2004-2014. In the article it was shown that agriculture in the EU countries is varied in terms of cost structure, and in the cluster II, including mostly the countries of the so-called “new” EU, intermediate consumption is of relatively larger significance for their cost structure. In the countries of the “old” EU an important role is played by the depreciation of buildings and external services. Stronger influence of capital-labour ratio on the payment to the factor of labour was observed in the cluster II countries. In those countries, increasing capital expenditures was a more efficient strategy to increase income.